2020
DOI: 10.2478/aut-2020-0008
|View full text |Cite
|
Sign up to set email alerts
|

Application of Silica Aerogel in Composites Protecting Against Thermal Radiation

Abstract: Aerogels are characterized by excellent insulation properties and a good resistance to high and low temperatures. The objective of this study was to investigate the effects of silica aerogel on thermal properties of textile–polymer composites. Aerogel was applied in protective clothing fabric to improve its heat resistance. The composites were produced by coating a fabric made of meta-aramid (polyamide–imide) yarns with a dispersion of polychloroprene latex and synthetic resins or an acrylic–styrene dispersion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…So it is a simpler way to apply aerogel. Similar findings were reported in our previous studies [53] concerning a textile-polymer composite produced by coating a meta-aramid fabric with a granular aerogel dispersion. The RHTI24 increased by approx.…”
Section: Aerogel Effects On Thermal Radiationsupporting
confidence: 92%
See 1 more Smart Citation
“…So it is a simpler way to apply aerogel. Similar findings were reported in our previous studies [53] concerning a textile-polymer composite produced by coating a meta-aramid fabric with a granular aerogel dispersion. The RHTI24 increased by approx.…”
Section: Aerogel Effects On Thermal Radiationsupporting
confidence: 92%
“…Jin et al [12] pointed to some problems with material homogeneity, with the main difficulty being the use of acetone as a solvent in the process of nonwoven impregnation with an aerogel dispersion. A similar problem was noted by Krzemińska et al [53] for a meta-aramid fabric coated with a latex dispersion with aerogel (100-700 μm particle size) as aerogel particles tended to be crushed in the process of coating. As a result, the obtained improvement of thermal resistance properties may be lower than expected.…”
Section: Aerogel Effects On Convective Heat Resistancesupporting
confidence: 67%
“…It has therefore been found that the lamination of aerogel composites is an effective solution to prevent the spread of the aerogel to the environment. The problem with aerogel crushing was also noticed by Krzemińska et al [ 59 ], who were coating fabric with a polymer dispersion with the addition of silica aerogel in the form of granules. Based on the SEM micrographs, the authors noted an approximate 50-fold reduction in the size of the aerogel particles as a result of applying a coating containing 6% aerogel to the fabric.…”
Section: Resultsmentioning
confidence: 80%
“…The most commonly used solution, especially in the protective clothing protecting against extremely low temperatures, is that of nonwoven composites consisting of a silica aerogel matrix and a reinforcing material, which is a nonwoven fabric [20]. The…”
Section: Introductionmentioning
confidence: 99%